BILINGUALISM POLICY IN SINGAPORE ELITE SCHOOLS - Wang Jiayan; Liu Junru; Wong Huiqi (Indonesian JELT, 2009)
The Singapore government has been promoting the mastery of the English language as well as the mother tongue since 1987 in the hope that Singaporeans can be fluent in both the working language and one related to their native roots. From then on, all Chinese schools are required to teach in the English language, and English is officially known as the first language of all students. This paper aims to study the policy’s background, specifically in the area of Mandarin, and find out whether this policy has managed to achieve its goals, how it has affected Singapore students’ language development in elite schools, how to improve the policy to benefit students in the future as well as provide some implications for enhancing Chinese teaching pedagogy.Keywords: Mother tongue,  the  English  Language,  elite school, Chinese teaching pedagogy.